Constituent processes of leaf senescence in Hordeum vulgare cv. Dyan - Afitlhile, Meshack Mosimanegape (Rhodes University, Faculty of Science, Botany Department, 1994)
Changes in chlorophyll content, carotenoid content and composition, abscisic acid and phaseic acid levels, hydrolytic enzyme activity and polypeptide pattern were monitored during senescence of the primary attached leaves of Hordeum vulgare L. cv. Dyan. Senescence occurred due to the normal course of leaf development or was induced by incubation of leaves in darkness. Loss of chlorophyll and total leaf protein was retarded in light whereas it continued rapidly in leaves from dark-incubated seedlings. Chlorophyll alb ratio increased with the progression of senescence, suggesting that chlorophyll b was referentially degraded during this process. Loss of total protein coincided with enhanced activity of acid and neutral proteases. In contrast, loss of chlorophyll was not accompanied by an increase inÂ· peroxidase activity, suggesting that this enzyme was not responsible for initiating chlorophyll breakdown. Carotenoid and abscisic acid levels were monitored in the same tissue extracts. The results obtained show that the increase in endogenous levels of abscisic acid, induced by senescence, correlated with enhanced epoxidation of the xanthophyll cycle, ie., increased conversion of zeaxanthin to antheraxanthin and all-trans-violaxanthin. In addition, an increase in abscisic acid levels occurred concomitant with a decrease in all-trans-violaxanthin and 9'-cis-neoxanthin, suggesting an apparent 1:1 relationship on a molar basis. It is therefore proposed that enhanced abscisic acid production, due to foliar senescence, arises from fluctuations in carotenoid turnover. Polypeptide patterns in isolated chloroplasts, purified thylakoid and stromal fractions were very similar for leaves incubated in either light or darkness. A decrease in intensity of bands was observed in isolated chloroplasts and stromal fractions. Intensity of bands in thylakoids remained unchanged with the progression of senescence. Protein standards of peroxidase and lipoxygenase co-migrated with proteins of the isolated chloroplast. Although tentative, some proteins of the chloroplast may be representative of precursors of hydrolytic enzymes which are known to increase during senescence.
Keywords: Leaves; Leaves -- Development